2010
DOI: 10.4197/med.17-3.6
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Awareness among Saudi Nursing Students

Abstract: Breast cancer is the most common cancer in women worldwide and its incidence is increasing in many countries. Nursing students are the future nurses who will have the opportunity to encourage and influence women to be breast aware. Breast-self examination is a simple and easy way to help women to detect any changes in the breasts. A quasiexperimental study was conducted to assess the effect of a Breast Cancer workshop on a group of 33 Saudi nursing students. The knowledge of breast cancer and competency in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 21 publications
6
22
0
1
Order By: Relevance
“…More than half of the nurses (67%) had good knowledge of BC signs and symptoms. These results are similar to that seen in other studies in Saudi Arabia (Yousuf, 2010), Nigeria (Odusanya and Tayo, 2001) and Singapore (Chong, 2004). This is in contrast to the findings of studies conducted in Nigeria (Akhigbe and Omuemu, 2009), Pakistan (Ahmed et al, 2006), and Morocco (Ghanem et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…More than half of the nurses (67%) had good knowledge of BC signs and symptoms. These results are similar to that seen in other studies in Saudi Arabia (Yousuf, 2010), Nigeria (Odusanya and Tayo, 2001) and Singapore (Chong, 2004). This is in contrast to the findings of studies conducted in Nigeria (Akhigbe and Omuemu, 2009), Pakistan (Ahmed et al, 2006), and Morocco (Ghanem et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Raising awareness will lead to early detection of breast cancer and play an important role in reducing complications and mortality. 17 Regarding the level of awareness results showed that 34.2% of the respondents had good knowledge. This level awareness is higher than that reported among students of University of Sharjah and Ajman of UAE and Jordan.…”
Section: Discussionmentioning
confidence: 95%
“…Generally, we can consider that items that have a mean equal or more the 3 have more agreement as perceived by the participant; those items include item number 5,12,13,10,11,14,15,4,18,1,7,9,8,6,19,26; those items are arranged from the most agreed items to the less agreed items by the participants. On the other hand, items that have a mean less than 3 have less agreement as perceived by the participants; those items include item number 3,16,20,22,2,21,17,25,24,23; those items are arranged from the most agreed items to the less agreed. In other word, the majority of participants believed that BC is dangerous to their health.…”
Section: Resultsmentioning
confidence: 99%
“…It is one of the studies in SA that aim to assess the perception of Saudi female adolescent toward BC in Riyadh city. A study conducted in SA estimated that the future burden of BC in SA is expected to increase by approximately 35% by 2025 [21]. In SA limited studies about Saudi female adolescent perception of BC.…”
Section: Discussionmentioning
confidence: 99%